Orders-of-magnitude enhancement in conductivity tuning in InGaZnO thin-film transistors via SiNx passivation and dual-gate modulation. Issue 3 (3rd July 2019) - Chen, ChangDong; Liu, ChenNing; Zheng, JiWen; Li, GongTan; Li, Shan; Wu, Qian; Wu, Jin; Liu, Chuan
Abstract : The mobility of pristine amorphous indium gallium zinc oxide ( a -IGZO) thin-film transistors (TFTs) is insufficient to meet the requirement of the future ultra-high-definition displays. Reported herein is the fabrication of hydrogenated long-channel IGZO TFTs exhibiting a transconductance and an on/off ratio that are orders of magnitude superior to those of the regular devices. The gate bias stability of the treated IGZO TFTs was greatly enhanced, with the threshold voltage shifting by less than 1 V after 1 h stress. Experimentally, the hydrogenation of the active layer was achieved via the deposition of a SiN x /SiO x bilayer on top of the IGZO via plasma-enhanced chemical vapor deposition followed by post-annealing under optimized conditions. The elemental depth profiles indicated that this enhanced performance originated from the hydrogen doping of the IGZO film. Furthermore, a dual-gate structure was fabricated to alleviate the deterioration of the subthreshold properties induced by the excess hydrogen doping.